KAJIAN KUALITAS AIR DAN KEANEKARAGAMAN JENIS FITOPLANKTON DI PERAIRAN WADUK PLUIT JAKARTA BARAT - Melati Ferianita Fachrul; Astri Rinanti; Diana Hendrawan; Aidian Satriawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2016)
Pluit reservoir located at Jl. Raya Pluit Selatan, Penjaringan West Jakarta in area of 80 hectares and water depth ranges ± 2-6 meters. This research aimed to analyze the water quality using the phytoplankton communities structure. To determine water quality condition of Pluit reservoir can be done by using phytoplankton as bioindicator of water pollution. The research was conducted in April up to July 2016 with 11 sampling points, that spread in inlet zone, the middle zone and the outlet zone of the reservoir. The physical and chemical parameters of water quality analysis will compared by Government Regulation No. 82 year 2001 of Water Quality and Water Pollution Control, the result show that DO (0.07-2.7 mg/l), BOD (5.59-67.11mg/l), COD (13.76-275.2mg/l), The values of diversity index H’=0.12 – 3.47, the value of Evenness (E) is 0.39– 0.95, that indicated the diversity of species is low and values of Dominace Index is tend to 0. The water condition classified as moderate or indicate semi-polluted waters.